Characterizing carbonate reservoir fracturing from borehole data – A case study of the Viséan in northern Belgium. (January 2020) - van der Voet, Eva; Muchez, Philippe; Laenen, Ben; Weltje, Gert Jan; Lagrou, David; Swennen, Rudy
Abstract: Fractured carbonate rocks are widely used as hydrocarbon or geothermal reservoirs. To provide a better understanding of the distribution and characteristics of such fractures, a general workflow will be presented for the characterization of fracturing from borehole data, by exploration and statistical analyses of integrated datasets. In a case study of Viséan limestones in a Belgian borehole, both cores and geophysical well logs were used to investigate which factors control the characteristics of partially open veins, which contribute to permeability. Relationships between multiple variables were tested statistically. Lithology, geochemistry and geophysical well log values were taken into account, as well as quantified veins, vugs and stylolites from cores. Although natural joint frequencies appeared hard to quantify from the available data, partially open vein characteristics could be well quantified. The results show that differential compaction controlled the development of fractures. Fracturing occurred preferentially in massive reefal buildup boundstones in contrast to layered wacke- to grainstones. Layer-parallel slip along bedding surfaces could also have reduced fracture development in the latter limestones. Frequencies of cemented veins and partially open veins are positively correlated, which suggests that the partially open veins result from either re-opening by dissolution, or (re-)opening due to a later fracturation phase. In summary, this multi-source study provides a workflow for fracture characterization from boreholes, as well as insights into the factors controlling the distribution and characteristics of partially open veins, which enhance reservoir permeability. Highlights: A workflow is proposed for the characterization of carbonate reservoir fracturing from boreholes. Cores and geophysical well logs were used to investigate which factors control the characteristics of partially open veins. Differential compaction controlled the development of fractures, contrasting between massive and layered limestones.